2017
DOI: 10.13189/ujar.2017.050501
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant and Nematicidal Effect of Trichoderma harzianum Rifai and Aqueous Extract of Azadirachta indica A. Juss. in Solanum lycopersicum L.

Abstract: The experiment was carried out with the objective of evaluating the biostimulating and nematicidal effect of Trichoderma harzianum Rifai "strain A-34" and aqueous extract of Azadirachta indica A. Juss. (neem) in Solanum lycopersicum L. (tomato) cv. "PR-92". Two trials were developed, the first in the seed germination process and the second in potting conditions for the treatments interaction and the inoculation of Meloidogyne spp. with tomato seedlings. The results showed that tomato seeds cv. "PR-92" treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This finding aligns with the results of a similar study conducted by Subedi (2022) on tomatoes, where Trichoderma viride demonstrated a significant reduction in the gall index (4.00) compared to the control (8.33). Baños et al (2017) also discovered that Trichoderma viride led to a 53.5% reduction in gall index caused by Meloidogyne spp. Furthermore, Baidya et al (2023) found that Trichoderma viride significantly decreased both the gall index (3.43) and the number of root galls per plant (88.86) in tomato, lending further support to our own findings.…”
Section: Root Gall Index and Number Of Root Galls Per Plantmentioning
confidence: 98%
“…This finding aligns with the results of a similar study conducted by Subedi (2022) on tomatoes, where Trichoderma viride demonstrated a significant reduction in the gall index (4.00) compared to the control (8.33). Baños et al (2017) also discovered that Trichoderma viride led to a 53.5% reduction in gall index caused by Meloidogyne spp. Furthermore, Baidya et al (2023) found that Trichoderma viride significantly decreased both the gall index (3.43) and the number of root galls per plant (88.86) in tomato, lending further support to our own findings.…”
Section: Root Gall Index and Number Of Root Galls Per Plantmentioning
confidence: 98%